2021
DOI: 10.3390/su14010128
|View full text |Cite
|
Sign up to set email alerts
|

Destination Familiarity and Perceived Attractiveness of Four Polish Tourism Cities

Abstract: Destination familiarity has been analyzed for many years as an important factor influencing the perceived attractiveness of a destination and its image. However, previous research has concentrated on this relation considering familiarity with a destination as a whole, while the issue of familiarity with particular elements of a destination has not been explored. The current research aimed to detect if and how familiarity with three selected elements of a destination, namely, tangible tourism attractions, event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 67 publications
2
9
0
Order By: Relevance
“…Specifically, destination managers can create new tourism activities and products for tourists to maintain the attractiveness of the destination. This suggestion can be supported by Szubert et al (2021), who found that perceived attractiveness is influenced by destination familiarity. The new tourism activities and products increase tourists’ curiosity about the destination which has the potential to increase their visit or revisit intentions.…”
Section: Discussionmentioning
confidence: 73%
“…Specifically, destination managers can create new tourism activities and products for tourists to maintain the attractiveness of the destination. This suggestion can be supported by Szubert et al (2021), who found that perceived attractiveness is influenced by destination familiarity. The new tourism activities and products increase tourists’ curiosity about the destination which has the potential to increase their visit or revisit intentions.…”
Section: Discussionmentioning
confidence: 73%
“…The variety of data processing methods can be categorized into the following groups: (a) statistical analysis ( 13 Due to the interest of researchers in attractiveness assessment and the variety of methods and techniques (52), we had the opportunity to create a solid database containing a high number of items, which were turned into in a large inventory of criteria; in total, 862 attractiveness attributes were inventoried. Along with the high interest in attractiveness assessment, the diversification of analysis techniques over time (e.g., surveys, statistics, GIS [10,63,64]) has increased the complexity of items finally available to us. The large and complex inventory of items ensures a better quantification of attractiveness in order to come as close as possible to an objective result.…”
Section: Deployment Analysismentioning
confidence: 99%
“…Tourist attractions are the driving force behind tourists visiting a destination, and are defined by richness of natural and socio-cultural potential with attractive value; others have commonly agreed on tourism attractions [10], tourist resources [11,12], or tourist physical features [13].…”
Section: Introductionmentioning
confidence: 99%
“…Findings suggest that the sense of presence positively mediates the relationships between holistic images and cognitive, affective and conative components. The second article of this axis by Szubert, Warcholik and Żemła [16] bridges a particular gap in the academic literature by focusing not only on familiarity as a whole, but by decomposing this concept into three elements: (1) tangible tourism attractions, (2) events, and (3) traditional cuisine and dishes. The authors aim to determine how the three types of familiarity impact the perceived attractiveness of a city destination using four Polish tourism cities as case studies.…”
Section: Overview Of Papers In This Special Issuementioning
confidence: 99%